The Role of Tadabbur Al-Qur'an in Forming the Islamic Worldview - Zubair Qudsi El Hanif Basyir; Abas Mansur Tamam (Universitas Darussalam Gontor, 2025)
The Islamic Worldview is the antithesis of various issues faced by the Muslim community, particularly those related to thought and civilisation. However, the ideas and concepts of the Islamic Worldview remain largely undercommunicated to the general public, especially through approaches that are practical, easy to understand, and impactful. This study aims to uncover the role of tadabbur Al-Qur'an as one of the easy and accessible approaches for anyone to cultivate the Islamic Worldview. This study employs a qualitative method with a library research approach, as the research subject or data collection is based on literature. The findings reveal that tadabbur possesses ontological, epistemological, and axiological dimensions that help construct a worldview based on tawhid, strengthen value internalization, and guide practical actions. Tadabbur not only enhances understanding of Qur’anic meanings but also initiates a reflective process that affects cognitive, affective, and psychomotor aspects. Therefore, tadabbur of the Qur’an serves as a strategic method to promote the Islamic Worldview across diverse societal levels.